Measuring Daily Activities in Dementia - Rhayel, Ashwak (My University, 2024)
Background: Dementia can impact different aspects of a person’s life, including the ability to conduct daily activities. Observing changes in one’s ability to conduct daily activities is an important outcome to consider when monitoring dementia progression. Caregivers, who may be family members or friends, play an essential part in supporting daily activities of the person living with dementia. However, aiding with daily activities and managing behavioural symptoms caused by dementia can contribute to caregiver distress. Therefore, the objectives of this thesis were: (1) to examine the psychometric properties of activity of daily living (ADL) and instrumental activity of daily living (IADL) questionnaires in older adults with dementia living in the community, and (2) to gain a comprehensive understanding of behaviours and actions associated with dementia care that are most distressing to caregivers. Methods: For the first objective, a systematic review guided by the COsensus-based Standards for the selection of health Measurement INstruments (COSMIN) guidelines was conducted. Measurement properties extracted included validity, reliability, and responsiveness. Risk of bias and quality assessments were performed for all included ADL and IADL questionnaires. For the second objective, we recruited and surveyed caregivers from Canada and the United States of America, caring for persons with dementia. Text responses were coded by two reviewers using the International Classification of Functioning, Disability and Health framework (ICF). Results: For the review, a total of 11 articles were included, yielding 7 different questionnaires. Internal consistency and reliability had sufficient ratings for all included measures, and convergent validity was acceptable overall. However, the quality of evidence across the studies varied. For the second manuscript, survey results identified 613 behaviours and actions distressing and meaningful to caregivers. Caregivers reported daily tasks such as toileting and self-care, as well as behavioural symptoms related to dementia such as agreeableness and impulse control, as distressing when caring for persons with dementia. Conclusions: This thesis focused on evaluating the functional deficits caused by dementia as well as the burden caregivers face when caring for persons living with dementia. Measures that assess functional impairment in persons with dementia can enable a greater understanding of the limitations associated with the condition as well as how to address them. A number of questionnaires that assess ADL and IADL impairments in community-dwelling older adults living with dementia have been identified. However, our results suggest that further research is needed on their psychometric properties. We also found that ADL and IADL impairments, in addition to psychological behaviours, are important from the caregivers’ perspective, further highlighting the importance of assessing these areas in dementia management and progression.
Keywords: Dementia; Daily Living Activities; Psychometric Properties; Caregivers